Persepsi Mahasiswa PAI dalam Pemanfaatan Teknologi Informasi Era Revolusi Industri 4.0 Pada Mata Kuliah Pembelajaran SKI di Madrasah - Muhammad Taufiqurrahman (Institut Agama Islam Negeri (IAIN) Tulungagung, 2019)
Nowadays, education is facing the fourth industrial era, also referred to industry 4.0 where technology is used as one of the tools or materials in teaching. The utilization of technology can be used by lecturers at class. Lecturers should have the ability to manage information technology as a supporting lectures media. Especially in this current era, the development of science and technology are all digitalized and automated. This study was conducted to see how students perceive the utilization of information and technology in Islamic Historical Culture subject at Islamic school by using quantitative descriptive methods obtained data from population samples and then analyzed in accordance with existing statistical methods it aims to obtain data through questionnaires that distributed to 50 samples then describe the result to get opinions students at PAI Program about information development. In this study, was found that 80% of students stated that information technology in the form of google drive was very useful in lectures. The use of technology is an effort to ask students to prepare themselves to compete with others in the 4.0 industrial revolution, especially in Islamic education.